Children's discourse and software use in a Western Cape primary school - Pallitt, Nicola (Centre for Film and Media Studies, 2024)
Children's discourse and software use were studied during computer lab sessions in a primary school in Athlone, South Africa. Conversation analysis and multimodal discourse analysis are used to study variations in children's discourse as they used email, a search engine and numeracy software . The children's limited range of discursive roles suggest a 'schooled' use of the software, since most of their activities are framed within the Initiation, Response, Feedback (IRF) pattern dominant in 'conventional' classroom discourse. Observations suggest that software is used in socially situated ways, thus challenging assumptions about the 'digital divide' and the determining power of technology. Software use is nonetheless associated with variations in discourse, marked by different configurations of an IRF discourse structure. Computer labs are unconventional classrooms, but not necessarily in ways that fulfill the radical claims of those who imagine that computers are a straightforward channel that allows children direct access to 'content' or 'the curriculum'. Consequently, 'ordinary' software applications such as search engines, browsers and email acquire different meanings in this context of use, marked by the power differentials implicit in South African educational practices, resourcing, and local classroom discourse. Transcribed video recordings of children's interactions in the computer lab allow a nuanced analysis of the nature of the work of schooling and learning in this context. These recordings reveal social negotiation, institutional and other power relations, and a marked scarcity of resources for communication via this channel. The observations suggest that teachers and children engage in complex discursive interactions around school, learning, and play as they use computers. Power relations established through these discourses are significant features of the children's experiences. Notions of 'access' are central to discussions of social equity and ICTs. This study reformulates 'access' to draw attention to the importance of children's limited access to certain discursive roles, and to the complex patterns of conflict and collaboration in the use of semiotic and other communicative resources in the computer lab. This study argues that the 'rules' of particular genres curtail children's access to particular discursive roles. The institutional 'rules' of classroom discourse play a central role, as do the algorithmic rules of the software. The analysis presented in the study will help teachers to understand the linguistic and semiotic processes central to children's learning in such environments. Workplace and consumer applications take on a particular discursive character in classroom use. The communicative possibilities of these applications are limited unless the children are initiated into the social groupings and discursive practices associated with their use. Although children often display creativity in exploiting the affordances of different types of software, there is an additional tension between the discourses they are assumed to be accessing (such as knowledge as inquiry or mathematical register) and the interplay of discourses suggested by the children's actual software use.